The role of accounting studies in student lifestyle and financial behavior - Jostan, Maria Natasha; Alimbudiono, Ria Sandra (Management and Entrepreneurship: Trends of Development, 2020)
This study aims to determine and understand the role of Accounting Studies in student lifestyle and financial behavior of accounting students, which will have an impact on their future accounting profession. Data collection is through interviews with 10 accounting students, academics and practitioners which obtained several results. The results of this study indicated that Accounting Studies plays a role in the lifestyle and financial thinking of accounting students, and will later be able to have an impact on the performance and daily life of the accounting profession in the future. Based on this analysis, overall it can be concluded that besides accounting studies, there is another factor to support the accountant mindset that is work environment, Mindset, financial behavior and accounting student life style obtained by accounting studies and it able to support future accounting profession. JEL Classification: M41, M410, G41